Self inflicted injury in a case of delusional parasitosis - Ghosh, Anuradha; Bhattacharyya, Debasis; Datta, Subhendu; Roy, Surjya; Bandyopadhyay, Gautam Kumar; Kundu, Muktananda; Sarkar, Ayan (International Journal of Research in Medical Sciences, 2024)
Delusional parasitosis also known as Ekbom’s syndrome, is a fixed, firm, false belief about a parasitic infestation of skin despite absence of evidence. Non-suicidal self injury (NSSI) is the deliberate and direct change leading to destruction of healthy body tissues e.g. skin cutting, scratching, burning, hitting of oneself and even enucleation of eye and amputation of body parts. We present a case of a 35-year-old male patient with delusional parasitosis for the past 3 months, referred from dermatology, who resorted to cutting himself on his arm and abdomen. He was treated successfully with anti-psychotics and had no further intention of self-harm.